ANALISIS TINDAK TUTUR ILOKUSI RAYUAN KOMEDIAN DARI INDONESIA TIMUR: TINJAUAN PRAGMATIK - Feberina Sagisolo Sagisolo; Siti Fatihaturrahmah Al Jumroh; Ismail Marzuki (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to describe and analyze persuasive illocutionary speech acts used by Eastern Indo- nesian comedians from a pragmatic perspective. The research method employed is descriptive qualitative with a pragmatic approach. Research data consists of comedians' utterances containing persuasive elements, obtained through observation, note-taking, and documentation techniques from comedy performances recorded in video format. Data analysis was conducted by classifying utterances based on types of illocutionary speech acts accord- ing to Searle's theory, then interpreting pragmatic functions and implicit meanings contained therein. The findings indicate that the most dominant form of persuasive illocutionary speech acts is expressive speech acts (43%), fol- lowed by directive (33%), and commissive speech acts (24%). Persuasion is used as a humor strategy to build closeness with the audience, create humorous effects, and convey social criticism indirectly. The cultural context of Eastern Indonesia plays an important role in shaping the meaning of persuasive illocutionary acts, especially through the use of local dialects, distinctive intonation, and representation of social realities. This research en- riches pragmatic studies, particularly speech acts in comedy discourse, and provides deep understanding of lan- guage use as a reflection of Eastern Indonesian cultural identity.